The Moderating Role of Profitability on the Impact of CSR on Firm Valuation - Muhammad Rizki Jayasasmita; Ifan Wicaksana Siregar (CV. Science Tech Group, 2025)
This study looks at how profitability functions as a moderator in the relationship between firm value and Corporate Social Responsibility (CSR) in mining businesses listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. Based on the theories of Stakeholder, Signaling, and Slack Resources, the study used a quantitative causal–associative approach using panel data from eight mining companies that regularly released sustainability and annual reports that adhered to Global Reporting Initiative (GRI) guidelines. Profitability is determined by Return on Assets (ROA), CSR by the CSR Disclosure Index, and firm value by Tobin's Q. To analyze the data, moderated regression analysis (MRA) was used. The findings show that firm value is not significantly impacted by CSR, and that the link between CSR and firm value is not moderated by profitability, which neither directly affects nor directly influences firm value. These results imply that profitability and corporate social responsibility (CSR) policies alone are not enough to determine firm value in the context of Indonesian mining businesses. Theoretically, the study challenges the assumption that CSR and profitability are always value-enhancing, while practically it implies that managers and regulators must reconfigure CSR into integrated business strategies that generate measurable social and economic impact.